2020
DOI: 10.1021/acsptsci.9b00081
|View full text |Cite
|
Sign up to set email alerts
|

A New Selective Pharmacological Enhancer of the Orai1 Ca2+ Channel Reveals Roles for Orai1 in Smooth and Skeletal Muscle Functions

Abstract: Store-operated calcium (Ca 2+ ) entry is an important homeostatic mechanism in cells, whereby the release of Ca 2+ from intracellular endoplasmic reticulum stores triggers the activation of a Ca 2+ influx pathway. Mediated by Orai1, this Ca 2+ influx has specific and essential roles in biological processes as diverse as lactation to immunity. Although pharmacological inhibitors of this Ca 2+ influx mechanism have helped to define the role of store-operated Ca 2+ entry in many cellular events, the lack of isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…The identification of a SOCE enhancer among a class of inhibitors has been reported in three previously published classes of modulators, with two of them described by us and represented by pyrtriazoles (AL-2T ( 43 ), NM-3G ( 44 ), Figure 5 ), 35 and biphenyl triazoles (compound 45 , Figure 5 ) 39 and one reported in the literature (IA65 ( 46 ), Figure 5 ). 40 A similar behavior is also shared by 2-APB ( 47 ), a well-known inhibitor of IP3 receptors and TRP channels. The compound is a SOCE modifier in Orai1- and Orai3-expressing cells, acting as SOCE enhancer at low concentrations, while high concentrations induce a transient increase followed by complete inhibition.…”
mentioning
confidence: 79%
“…The identification of a SOCE enhancer among a class of inhibitors has been reported in three previously published classes of modulators, with two of them described by us and represented by pyrtriazoles (AL-2T ( 43 ), NM-3G ( 44 ), Figure 5 ), 35 and biphenyl triazoles (compound 45 , Figure 5 ) 39 and one reported in the literature (IA65 ( 46 ), Figure 5 ). 40 A similar behavior is also shared by 2-APB ( 47 ), a well-known inhibitor of IP3 receptors and TRP channels. The compound is a SOCE modifier in Orai1- and Orai3-expressing cells, acting as SOCE enhancer at low concentrations, while high concentrations induce a transient increase followed by complete inhibition.…”
mentioning
confidence: 79%
“…Several chemical inhibitors [ 23 , 24 , 25 , 26 , 27 ] as well as potentiators of SOCE [ 28 , 29 , 30 ] have been reported. However, 2-aminoethyl diphenylborinate (2-APB, Figure 1 ) remains the best characterized compound used to modulate store-operated CRAC channels, despite of its effects on other known targets [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used the MDA-MB-231 breast cancer cell line to screen our newly developed 2-APB analogues for their action on SOCE, using a fluorometric imaging plate reader (FLIPR)-based Ca 2+ imaging assay. FLIPR assays with MDA-MB-231 cells have been used in the past for discovery of SOCE modulators [ 26 , 30 , 72 ]. Earlier reports using RNA silencing have shown that SOCE in MDA-MB-231 cells is conducted by STIM1 and Orai1 [ 18 , 26 , 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the focus of this study was to identify novel SOCE negative modulators for the treatment of AP, the profile of compound 47 was not investigated further, but its discovery supports the idea that minor structural modifications of SOCE inhibitors can interfere with channel gating and produce activators, as already observed for pyrtriazoles (AL-2T ( 57 ), NM-3G ( 58 ); Figure 5 ) 16 and for another recently described SOCE enhancer (IA65 ( 59 ), Figure 5 ). 22 47 therefore represents an enhancer of SOCE from a third distinct class of modulators and provides grounds to develop models to understand the mechanism by which this occurs.…”
Section: Results and Discussionmentioning
confidence: 99%